Dimensions of democracy and digital political activism on Hopewell Chin’ono and Jacob Ngarivhume Twitter accounts towards the July 31st demonstrations in Zimbabwe - Payidamoyo Nyoka; Mary Tembo (Taylor and Francis Group, 2023)
Using a qualitative research approach, this study provides an inquiry into the nature of democracy and digital political activism discourses on @Hopewell Chin’ono and @Jacob Ngarivhume prior to the 31st July demonstrations. Alternative communications spaces have revolutionised political communication in Zimbabwe. In Zimbabwe, political polarisation has created a monolithic voice in the mainstream media. In the “Second Republic”, digital activism is a growing phenomenon where subalterns question the state. This study is guided by Manuel Castells’ Power and Counter Power Theory. Data gathered using netnography was analysed using critical discourse analysis. Findings show that digital activism has turned into social media “dissidence”, calling for the resignation of the government officials including the Executive through 31st demonstrations. There is an intimate relationship between digital democracy and digital activism, enabling political advocacy and lobbying. Twitter is used to safeguard the lives of activists. Religious discourses were used by both Jacob Ngarivhume and Hopewell Chin’ono as they drummed up support for the July 31st demonstrations.